1996
DOI: 10.1111/j.1476-5381.1996.tb15464.x
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic modulation by L‐glutamate and GABA of sympathetic co‐transmission in rat isolated vas deferens

Abstract: 1 The modulatory effects of L-glutamate and its structural analogues, and of y-aminobutyric acid (GABA), on sympathetic co-transmission were studied in the rat isolated vas deferens exposed to electrical field stimulation (EFS). 2 Application of exogenous L-glutamate caused a concentration-dependent (1 /M -3 mM) inhibition of the rapid twitch component of the biphasic EFS contraction. However, L-glutamate (1 MM-3 mM) had a minimal effect on the phasic contraction induced by exogenous adenosine 5'-triphosphate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Our present study could thus provide further evidence for the modulation by GABA of renal functions, although we did not measure changes in urine formation. Kwan et al (1996) have demonstrated that GABA suppresses electrical stimulation-evoked purinergic contraction of the isolated rat vas deferens in the presence of phentolamine. In our present study, prazosin even at the high dose (30 nM) failed to abolish the RNS-induced PP response; about 20 ± 30% of the increases in PP still remained, and addition of rauwolscine failed to suppress this residual PP response.…”
Section: Discussionmentioning
confidence: 99%
“…Our present study could thus provide further evidence for the modulation by GABA of renal functions, although we did not measure changes in urine formation. Kwan et al (1996) have demonstrated that GABA suppresses electrical stimulation-evoked purinergic contraction of the isolated rat vas deferens in the presence of phentolamine. In our present study, prazosin even at the high dose (30 nM) failed to abolish the RNS-induced PP response; about 20 ± 30% of the increases in PP still remained, and addition of rauwolscine failed to suppress this residual PP response.…”
Section: Discussionmentioning
confidence: 99%
“…Rats [151] Inhibitory Rat VD [152] GABA Inhibitory Rats [153] Inhibitory Rat VD [152] Rat ischiocavernosus [154] Serotonin Inhibitory Humans [29] Rats: 5-HT 2C agonists [155] Rats: 5-HT 1B agonists [48] Rats: 5-HT 2B agonists [156] Inhibitory Rat VD and SV [157] Excitatory Rats: 5-HT 1A agonists [48] Excitatory Mouse VD: 5-HT 1A stimulation [158] Angiotensin II Inhibitory Rats [159] Excitatory Rat VD [160] Oxytocin Excitatory Rats [71] Humans [73,161] Excitatory Rat and rabbit: prostatic urethra, bladder neck and ejaculatory duct [76] No effect Rat and rabbit: VD, SV, epididymis, and prostate [76] Nitric oxide Excitatory (MPOA)…”
Section: Excitatorymentioning
confidence: 99%
“…The prostatic half of the rat vas deferens was used because, in this part, the purinergic mechanism responsible for the initial rapid twitch in response to EFS is dominant (Kwan et al 1996). Under our experimental conditions the two phases were not always clearly distinguishable.…”
Section: Discussionmentioning
confidence: 96%
“…g-Aminobutyric acid (GABA) is quantitatively one of the most important inhibitory transmitters in the CNS. It has been shown that GABA is also present in peripheral tissues such as the bladder (Maggi et al 1985), fallopian tube (Erdo È et al 1982) and rat vas deferens (Kwan et al 1996).…”
mentioning
confidence: 99%
See 1 more Smart Citation